2007
DOI: 10.1183/09031936.00088907
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosain the home environment of newly infected cystic fibrosis patients

Abstract: The source of acquisition of Pseudomonas aeruginosa in cystic fibrosis (CF) patients remains unknown. Patient-to-patient transmission has been well documented but the role of the environment as a source of initial infection is as yet unclear.In the present study, the origin of the first P. aeruginosa isolate in CF patients was investigated by comparing the P. aeruginosa genotype(s) from newly infected patients with genotypes of P. aeruginosa isolates from the home environment and from other patients from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 35 publications
5
48
2
Order By: Relevance
“…One of the characteristics of Pseudomonas aeruginosa is high resistance to the types of antibiotics (Poole, 2004;Estahbanati, Kashani, & Ghanaatpisheh, 2002;Ebrahimzadeh Shiraz, Rezaei Yazdi, & Alijanianzadeh, 2017). Schelstraete et al showed that patients with cystic fibrosis had received Pseudomonas aeruginosa out of the home environment (such as the dental environment) (Schelstraete et al, 2007). Therefore, the transmission of this pathogen to patients with weakened immune system in dental centers is a great concern.…”
Section: Discussionmentioning
confidence: 99%
“…One of the characteristics of Pseudomonas aeruginosa is high resistance to the types of antibiotics (Poole, 2004;Estahbanati, Kashani, & Ghanaatpisheh, 2002;Ebrahimzadeh Shiraz, Rezaei Yazdi, & Alijanianzadeh, 2017). Schelstraete et al showed that patients with cystic fibrosis had received Pseudomonas aeruginosa out of the home environment (such as the dental environment) (Schelstraete et al, 2007). Therefore, the transmission of this pathogen to patients with weakened immune system in dental centers is a great concern.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic environments, A. xylosoxidans was detected in hand-washing sinks and shower drains but not in toilet bowls. The colonization of sinks and shower drains by P. aeruginosa has already been described in home environment studies (43,44). These materials are in contact with soap as well as with chemical products used for cleaning, many of them containing alkyldimethylbenzylammonium chloride, a quaternary ammonium compound.…”
Section: Discussionmentioning
confidence: 99%
“…304 Similarly, in the homes of people with CF, P. aeruginosa was detected most often from shower drains and bathroom drainpipes. 305,306 While P. aeruginosa was recovered from 34% of the homes of newly infected people with CF (6% of samples), only 9 (18%) of 50 paired environmental and patient isolates were the same strain. 306 It remains unclear whether these P. aeruginosa strains were transmitted from the individuals with CF to the home environment or vice versa, but it suggests that cleaning and disinfection efforts in the homes of people with CF should focus on bathroom drains.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%